2022
DOI: 10.1111/exd.14671
|View full text |Cite
|
Sign up to set email alerts
|

Keloid: Genetic susceptibility and contributions of genetics and epigenetics to its pathogenesis

Abstract: Keloid, characterized by fibroproliferative disorders of the skin, can be developed in people of different genders, ages and ethnicities. Keloid can appear in any part of the body but are especially common on the earlobe, upper torso and triangular muscle. The genetic heterogeneity and susceptibility of KD (keloid) vary among different races and ethnicities. Studies have found that multiple loci on multiple chromosomes are associated with the pathogenesis of KD, and specific gene variants may also be involved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…59 Genetics and epigenetics analysis reveals inherent differences between KFs and NFs such as genetic loci, DNA methylation, and non-coding RNA among different races. 60 Transcriptomics analysis suggests that KFs are featured by 'malignant-like' behaviors in terms of cell proliferation and migration. 61 However, we did not find the overexpression of UCHL1 in dermal fibroblasts facilitated cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…59 Genetics and epigenetics analysis reveals inherent differences between KFs and NFs such as genetic loci, DNA methylation, and non-coding RNA among different races. 60 Transcriptomics analysis suggests that KFs are featured by 'malignant-like' behaviors in terms of cell proliferation and migration. 61 However, we did not find the overexpression of UCHL1 in dermal fibroblasts facilitated cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of keloids is likely multifactorial and hinges on a constellation of factors, including genetic predisposition ( 26 34 ), inflammation ( 35 39 ), mechanical stress ( 40 43 ), tissue hypoxia ( 44 48 ), delayed-type hypersensitivity ( 49 ), and metabolic dysfunction ( 50 , 51 ). Familial cases of autosomal dominant inheritance with incomplete clinical penetrance and variable expression have been described ( 52 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, reduced expression of potential anti-inflammatory mediators, such as IL-34 and IL-37, has been reported ( 85 , 87 , 95 , 96 ). Single-cell RNA sequencing and spatial transcriptomics ( 72 , 97 99 ), as well as epigenetics ( 34 , 100 ) are emerging fields utilized to reveal potential pathophysiological features of keloids. One single-cell RNA sequencing study identified a distinct macrophage-centered communication regulatory network that may favor transition and proliferation of M2 macrophages ( 72 ).…”
Section: Introductionmentioning
confidence: 99%
“…Keloid is a dermatofibrosis characterized by excessive fibroblast proliferation and collagen deposition that invades normal tissue beyond its original borders, often secondary to trauma, surgery, and inflammation ( 1 , 2 ), with an incidence of 5–15% during wound healing ( 3 ). Keloid often develops in patients with a family history of the disease or dark-skinned patients ( 4 , 5 ). Due to the high recurrence rate, this disease remains one of the most pressing clinical challenges.…”
Section: Introductionmentioning
confidence: 99%